ANALYSIS OF THE CRIMINAL ACT OF ANIMAL ABUSE (STUDY OF DECISION NUMBER: 72/PID.C/2023/PN.PDG) - Vira Dalillah; Syaiful Munandar (Fakultas Hukum Universitas Djuanda, 2024)
Asia For Animals Coalition announced that Indonesia is the country with the highest number of animal content uploaded on social media. There is 1,626 content showing animal abuse originating from Indonesia, according to data collected from YouTube, Facebook and TikTok between July 2020 and August 2021. However, there is still a lot of similar content from locations that have not been identified. Animal Defender Indonesia noted that the high number of animal abuse videos uploaded from Indonesia was due to